Baroque viola bowing techniques used in modern viola for “Concerto in G Major, 3rd Movement” by Georg Philipp Telemann / Iffah Rasyidah Shahabudin - Shahabudin, Iffah Rasyidah (2020)
Baroque bowing technique is the bowing techniques used by the strings player in Baroque period, which is on the eighteenth century. The eighteenth century was a magnificence century for viola history. It is on the grounds that viola has moved from a steady voice into an essential job as a performance instrument. Prior to 1740, the viola is typically filled in as a backup job as they give the middle voices in harmony textures and they ordinarily barred from trio sonatas. Georg Philipp Telemann was one of the first composers who had brought up viola as a solo instrument. Telemann composed several compositions for viola and one of his famous viola composition is the Concerto in G Major. This concerto had become a famous solo concerto played by the intermediate viola players. During the Baroque time, the bows were attempted to the "rule of the down bow" which drove the bowing models. Expound music tended towards move style, short note music, which the Baroque bow could arrange well. In any case, as players moved towards legato (long-bow), the Baroque bows were unsuited and makers like Francois Tourte started upgrading with new plans and materials. Tourte's bows unequivocally went through a transitional time of experimentation before picking the propelled style of bow making with a strong opposite camber, short strong head, and even thickness proposed to give power both in to a great extent bowing, and close and far from the frog. For this study, the author selected one of the Telemann’s composition, entitled, “Concerto of G Major, 3rd movement” to look forward the bowing techniques used in baroque period, to apply it on the modern viola. The main purpose of this study is to interpret the “Concerto of G Major, 3rd movement” by G.P Telemann and to find the Baroque bowing techniques used to play the concerto using a modern viola. Several interviews have been done by the author in order to get the finding of the study. The interview was conducted among two professional baroque viola player in Malaysia. The author used semi-structured method of questionnaire and provides about five questions for each participants. The author also analyse the “Concerto of G Major, 3rd movement” score in order to investigate the way to interpret and to play the concerto. Following some in-depth analysis, some recommendations for the study are presented.